Mapping Cases of Corruption by Civilian Public Agents in the Executive Branch of the Federal Government: An Exploratory Descriptive Study - Assumpção Silva, Flávio de Arruda; Moraes, Cecília Arlene (Journal of Law and Corruption Review, 2021)
The fight against corruption has been intensified to minimize the harmful effects on society through the adoption of preventive and combat measures by the State. This study aims to map cases of corruption committed by civilian public agents in the Executive Branch of the Federal Government from 2016 to 2018, resulting from administrative sanctions, demonstrating the links of the agents involved with the public administration, the identification of the organs and careers with the highest incidence, the method of accessing the position, and information that can contribute to more effective decision-making for the containment of the crime. A descriptive exploratory research with a quantitative approach in numerical reports showed that administrative sanctions accounted for 0.135% of the total number of civilian public agents nationally. The organ and career with the highest occurrence of crimes routinely carry out work focused on public service. The states of Rio de Janeiro with 194 cases and Mato Grosso with 0.343% stand out, presenting the highest incidence of cases in absolute and proportional terms, respectively.